Design And Develop A Web-Based Printing Service Information System At CV MARPRINT OFFSET And SCREEN PRINTING - Apriani, Gustian; Sharyanto, Sharyanto; Saputro, Joko (Journal of Engineering, Technology and Computing (JETCom), 2024)
The title of this research is "Design and Development of Web-Based Printing Service Information System at CV Marprint Offset and Screen Printing." The research background emphasizes the importance of adapting information technology in human resource management, especially in the manual printing service process. CV Marprint faces various problems, including slow administrative processes, limited data accessibility, and lack of transparency in employee performance evaluations. This research aims to design and implement an efficient and effective web-based information system, focusing on the ordering, production, and delivery processes of printing services. The research methods used include observation, interviews, literature review, system design, and testing. The expected results are to provide a significant contribution to CV Marprint in improving the efficiency and effectiveness of printing services, as well as to serve as a reference for other companies in the printing industry. With the implementation of the appropriate information system, it is hoped that CV Marprint can enhance its competitiveness in the digital era and achieve organizational goals more optimally.